2014
DOI: 10.4049/jimmunol.1302902
|View full text |Cite
|
Sign up to set email alerts
|

ATP Modulates Acute Inflammation In Vivo through Dual Oxidase 1–Derived H2O2 Production and NF-κB Activation

Abstract: Dual oxidase 1 (Duox1) is the NADPH oxidase responsible for the H2O2 gradient formed in tissues after injury to trigger the early recruitment of leukocytes. Little is known about the signals that modulate H2O2 release from DUOX1 and whether the H2O2 gradient can orchestrate the inflammatory response in vivo. In this study, we report on a dominant-negative form of zebrafish Duox1 that is able to inhibit endogenous Duox1 activity, H2O2 release and leukocyte recruitment after tissue injury, with none of the side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 58 publications
5
77
0
Order By: Relevance
“…4C). This is in agreement with a recent report that identified increased NFκB activity after wounding in zebrafish larvae downstream of wound-induced H 2 O 2 de Oliveira et al, 2014). Because early wound signals like H 2 O 2 have been shown to modulate regeneration (Yoo et al, 2012), we sought to determine whether NFκB activation was required for mmp9 expression.…”
Section: Mmp9 Influences Early Leukocyte Recruitment During Caudal Fisupporting
confidence: 68%
“…4C). This is in agreement with a recent report that identified increased NFκB activity after wounding in zebrafish larvae downstream of wound-induced H 2 O 2 de Oliveira et al, 2014). Because early wound signals like H 2 O 2 have been shown to modulate regeneration (Yoo et al, 2012), we sought to determine whether NFκB activation was required for mmp9 expression.…”
Section: Mmp9 Influences Early Leukocyte Recruitment During Caudal Fisupporting
confidence: 68%
“…In contrast, PLA2 and noncanonical arachidonate metabolites, via a 5-oxo-ETE receptor, have been shown to mediate hyposmolarity-induced leukocyte chemotaxis and rapid leukocyte recruitment to sites of tissue damage in zebrafish (45). These differences might be explained by the absence of tissue damage and, therefore, full barrier integrity in newly hatched embryos compared with a local wounded tissue where DAMPs are rapidly released, such as ATP that activates purinergic receptors and signals through alternate pathways (46,47). Unfortunately, we failed to determine the contribution of PLC downstream TRPV4 activation, because pharmacological inhibition of PLC drastically induced IL-1b transcript levels, probably reflecting the essential role of PLC-d1 in skin stem cell lineage commitment (48), which results in the induction of inflammation in PLC-d1-deficient mice (49).…”
Section: Discussionmentioning
confidence: 62%
“…Additionally, it has been shown in vitro that H 2 O 2 is able to modulate the function of redox-sensitive transcription factors (13,14) and to influence the gene expression of proinflammatory molecules, such as IL-1b or CXCL8 (15)(16)(17)(18). Recently, we have further reported that Duox1-derived H 2 O 2 is involved in NF-kB activation in wound healing (19). Importantly, we have also found that CXCL8 zebrafish homologs, Cxcl8-l1 and Cxcl8-l2, are crucial for neutrophil recruitment upon wounding and that they are able to dictate neutrophil behavior and to influence later tissue regeneration in zebrafish larvae (10).…”
mentioning
confidence: 99%